2009
DOI: 10.1016/j.canlet.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

PAX3–FKHR sensitizes human alveolar rhabdomyosarcoma cells to camptothecin-mediated growth inhibition and apoptosis

Abstract: Patients with alveolar rhabdomyosarcoma (ARMS) have poorer response to conventional chemotherapy and lower survival rates than those with embryonal RMS (ERMS). By high-throughput screening, we identified camptothecin as an ARMS-selective inhibitor. Camptothecin more efficiently inhibited proliferation and induced apoptosis in Rh30 (ARMS) than RD (ERMS) cells. Ectopic expression of the PAX3-FKHR (PF) fusion protein in RD cells significantly increased sensitivity, whereas siRNA knockdown of PF decreased sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…It has been reported that camptothecin induces apoptosis and inhibits proliferation of RD cells [33].…”
Section: Determination Of Induced Apoptosis In Rd Cells By Flow Cytommentioning
confidence: 99%
“…It has been reported that camptothecin induces apoptosis and inhibits proliferation of RD cells [33].…”
Section: Determination Of Induced Apoptosis In Rd Cells By Flow Cytommentioning
confidence: 99%
“…Rh30, Rh41, RD, HEK293T, NIH3T3 cells, and the establishment of PAX3-FKHR knockdown (KD1) and control (CON) stable clones of Rh30 have been described previously [57]. Phenol red–free Dulbecco’s modified Eagle’s medium (Invitrogen, Carlsbad, CA) was used for all luminescence assays.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of total RNA, preparation of cDNA, PCR primers for PAX3-FKHR and glucose-6-phosphate dehydrogenase (GAPDH), the conditions for PCR, and the quantitation of mRNA levels have been previously described [5, 7, 8]. Briefly, the cycle threshold (Ct) values of each gene of interest and of GAPDH were calculated for each sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RT-CES assay (ACEA Biosciences, San Diego, CA) was used to monitor real-time cell proliferation of HepG2 cells as described previously, and the cell index was derived from the cell status-based cellelectrode impedance (Zeng et al, 2009). In brief, approximately 1 ϫ 10 4 cells were seeded in growth medium onto a 96x e-plate (ACEA Biosciences) and allowed to attach and spread for 12 h before real-time cell proliferation was monitored; the cell index was automatically determined every 60 min for 72 h.…”
Section: Methodsmentioning
confidence: 99%